Inflammatory factors and the risk of urolithiasis: a bidirectional Mendelian randomization study - Huang, Kunyuan; Peng, Zheng; Zha, Cheng; Li, Wei; Deng, Guanyun; Chen, Xiaolong; Luo, Yuting; Ji, Zhiqiang; Wang, Qing; Jiang, Kehua (Frontiers in Medicine, 2024)
Background Urolithiasis is a prevalent condition encountered in urology. Over the past decade, its global incidence has been on an upward trajectory; paired with a high recurrence rate, this presents considerable health and economic burdens. Although inflammatory factors are pivotal in the onset and progression of urolithiasis, their causal linkages remain elusive. Method Mendelian randomization (MR) is predicated upon genome-wide association studies (GWASs). It integrates bioinformatics analyses to reveal causal relationships between exposures and outcomes, rendering it an effective method with minimized bias. Drawing from a publicly accessible GWAS meta-analysis comprising 8,293 samples, we identified 41 genetic variations associated with inflammatory cytokines as instrumental variables. Outcome data on upper urinary tract stones, which included renal and ureteral stones (9,713 cases and 366,693 controls), and lower urinary tract stones, including bladder and urethral stones (1,398 cases and 366,693 controls), were derived from the FinnGen Consortium R9 dataset. By leveraging the bidirectional MR methodology, we aimed to decipher the causal interplay between inflammatory markers and urolithiasis. Results Our study comprehensively elucidated the association between genetic inflammatory markers and urolithiasis via bidirectional Mendelian randomization. Post-MR analysis of the 41 genetic inflammation markers revealed that elevated levels of circulating interleukin-2 (IL-2) (OR = 0.921, 95% CI = 0.848–0.999) suggest a reduced risk for renal stone disease, while heightened stem cell growth factor beta (SCGF-β) (OR = 1.150, 95% CI = 1.009–1.310) and diminished macrophage inflammatory protein 1 beta (MIP-1β) (OR = 0.863, 95% CI = 0.779–0.956) levels suggest an augmented risk for lower urinary tract stones. Furthermore, renal stone disease appeared to elevate IL-2 (β = 0.145, 95% CI = 0.013–0.276) and cutaneous T cell-attracting chemokine (CTACK) (β = 0.145, 95% CI = 0.013–0.276) levels in the bloodstream, whereas lower urinary tract stones were linked to a surge in interleukin-5 (IL-5) (β = 0.142, 95% CI = 0.057–0.226), interleukin-7 (IL-7) (β = 0.108, 95% CI = 0.024–0.192), interleukin-8 (IL-8) (β = 0.127, 95% CI = 0.044–0.210), growth regulated oncogene alpha (GRO-α) (β = 0.086, 95% CI = 0.004–0.169), monokine induced by interferon-gamma (MIG) (β = 0.099, 95% CI = 0.008–0.191) and macrophage inflammatory protein 1 alpha (MIP-1α) (β = 0.126, 95% CI = 0.044–0.208) levels. Conclusion These discoveries intimate the instrumental role of IL-2 in the onset and progression of upper urinary tract stones. SCGF-β and MIP-1β influence the development of lower urinary tract stones. Urolithiasis also impacts the expression of cytokines such as IL-2, CTACK, IL-5, IL-7, IL-8, GRO-α, MIG, and MIP-1α. There is a pressing need for further investigation to ascertain whether these biomarkers can be harnessed to prevent or treat urolithiasis.